Implementation options for DNA-based identification into ecological status assessment under the European Water Framework Directive. (1st July 2018) - Hering, Daniel; Borja, Angel; Jones, J.Iwan; Pont, Didier; Boets, Pieter; Bouchez, Agnes; Bruce, Kat; Drakare, Stina; Hänfling, Bernd; Kahlert, Maria; Leese, Florian; Meissner, Kristian; et al.
Abstract: Assessment of ecological status for the European Water Framework Directive (WFD) is based on "Biological Quality Elements" (BQEs), namely phytoplankton, benthic flora, benthic invertebrates and fish. Morphological identification of these organisms is a time-consuming and expensive procedure. Here, we assess the options for complementing and, perhaps, replacing morphological identification with procedures using eDNA, metabarcoding or similar approaches. We rate the applicability of DNA-based identification for the individual BQEs and water categories (rivers, lakes, transitional and coastal waters) against eleven criteria, summarised under the headlines representativeness (for example suitability of current sampling methods for DNA-based identification, errors from DNA-based species detection), sensitivity (for example capability to detect sensitive taxa, unassigned reads), precision of DNA-based identification (knowledge about uncertainty), comparability with conventional approaches (for example sensitivity of metrics to differences in DNA-based identification), cost effectiveness and environmental impact. Overall, suitability of DNA-based identification is particularly high for fish, as eDNA is a well-suited sampling approach which can replace expensive and potentially harmful methods such as gill-netting, trawling or electrofishing. Furthermore, there are attempts to replace absolute by relative abundance in metric calculations. For invertebrates and phytobenthos, the main challenges include the modification of indices and completing barcode libraries. For phytoplankton, the barcode libraries are even more problematic, due to the high taxonomic diversity in plankton samples. If current assessment concepts are kept, DNA-based identification is least appropriate for macrophytes (rivers, lakes) and angiosperms/macroalgae (transitional and coastal waters), which are surveyed rather than sampled. We discuss general implications of implementing DNA-based identification into standard ecological assessment, in particular considering any adaptations to the WFD that may be required to facilitate the transition to molecular data. Graphical abstract: Source: http://dnaqua.net . Image 1 Highlights: eDNA and metabarcoding are options for complementing and replacing morphological identification. These methods are differently well suited for assessing Biological Quality Elements (BQEs). eDNA is well suited for assessing the fish fauna. Remaining challenges for all BQEs include the modification of assessment indices and completing barcode libraries. Methods are least suited for BQEs that are surveyed rather than sampled (e.g. macrophytes).